The Civil Wars in Chile : (or The Bourgeois Revolutions that Never Were) - Zeitlin, Maurice, 1935- (Book collections on Project MUSE., 1984)
This penetrating sociological study of the causes, consequences, and historical meaning of the civil wars in mid- and late-nineteenth century Chile argues that they were abortive bourgeois revolutions fought out among rival segments of Chile's dominant class. Indeed, it concludes that, in general, not only class but also intraclass struggles can be decisive historically, especially at transitional moments. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.